Potensi Karbon dari Bunga Cemara Laut (Casuarina Equisetifolia) sebagai Sumber Material Maju berdasarkan Hasil Uji Proksimat - Novel, Dheo Shalsabilla; Putri, Natasya Alya; Karsa, Dion Randi; Izanel, Rezi Ananta; Jannah, Miftahul; Khaliq, Feni Kurnia; Nizar, Umar Kalmar (Departemen Kimia FMIPA UNP, 2025)
This study explores the potential of Sea Pine Flowers from Pantai Pasir Jambak, Kota Padang, as a carbon source for advanced materials through carbonization. Carbon is generated by the incomplete carbonization process, which breaks down organic components. It can be obtained from organic waste materials that contain cellulose, hemicellulose, and lignin. Carbonization was performed at 350˚C for durations of 1 hour, 1.5 hours, 2 hours, and 2.5 hours. Analysis results revealed vapor content ranging from 2.18% to 2.69%, ash content from 4.44% to 8.06%, and bound carbon content from 89.25% to 92.88%. The highest bound carbon content was achieved at 350˚C for 1 hour (C-60). All results meet the SNI 06-3730-1995 standards. Low vapor and controlled ash content indicate high-quality carbon. This study confirms that Sea Pine Flowers have significant potential for advanced material applications as a high-quality carbon source.